Evaluating density forecasts with applications to financial risk management - Diebold, Francis X. (Institutional Knowledge at Singapore Management University, 1998)
We propose methods for evaluating density forecasts. We focus primarily on methods that are applicable regardless of the particular user’s loss function. We illustrate the methods with a detailed simulation example, and then we present an application to density forecasting of daily stock market returns. We discuss extensions for improving suboptimal density forecasts, multi-step-ahead density forecast evaluation, multivariate density forecast evaluation, monitoring for structural change and its relationship to density forecasting, and density forecast evaluation with known loss function.